Strains of the Song 19 Hours: Music as a Keeper of Awareness for Jakarta-Palembang AKAP Drivers - Mukhlis Mukhlis; Ifwanul Hakim; Khaerul Saleh (Universitas Negeri Medan, 2022)
AKAP bus is cross-city and provincial transportation in Indonesia. This research aims to observate the songs playlist on AKAP bus by looking at three aspects; form, function, and meaning. The purpose of this study consists of: 1) knowing the form of the song that is presented; 2) find out the function of the songs along the bus trips; 3) find out the meaning of the song. The method used in this research is a qualitative approach. The process of searching for data and information is carried out using interviews and field observations by recording audio and video. This study found the results that the type of music used on the Jakarta-Palembang AKAP Bus for the duration of the 19-hour journey is dominated by Dangdut, Indonesian Pop, and Regional Pop songs. The driver plays a playlist of songs randomly and repeatedly.